Hubungan antara Pengetahuan, Sikap, dan Perilaku mengenai Vulva Hygiene terhadap Kejadian Keputihan Patologis pada Siswi SMPN 1 Selemadeg Barat, Tabanan, Bali - Dayana Puspawarna; Anak Agung Sri Agung Aryastuti; Sayu Widiawati (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
[The Relation Between Knowledge, Attitude, and Behavior about Vulva Hygiene toward Pathological Vaginal Discharge in Female Students of SMPN 1 Selemadeg Barat, Tabanan, Bali] Reproductive health refers to a healthy reproductive system on all levels, including physical, social, psychological, and spiritual. Poor reproductive health in women accounts for 33% of the overall disease burden affecting women worldwide. Up to 75% of women worldwide have experienced vaginal discharge at least once in their lifetime, with 45% experiencing it twice or more. There are two types of vaginal discharge: physiological and pathological. Infections of the reproductive organs lead to athological vaginal discharges.. Vulva hygiene is one of the causes of infection. The purpose of this study was to examine the association between knowledge, attitudes, and behavior about vulva hygiene and the incidence of pathological vaginal discharge in female students at SMPN 1 Selemadeg Barat. This research is a cross-sectional study. The subjects were female students at SMPN 1 Selemadeg Barat who met the inclusion and exclusion criteria. A questionnaire was used to collect data in November 2023 and analyzed univariately and bivariately using the chi-square method. This research involved 60 respondents with an age distribution of 37 people who are 13 years old (61.7%), then 21 people are 14 years old (35.0%) and 2 people who are 12 years old (3.3%). The result indicated that the majority of respondents had high knowledge (60%), attitudes (61.7%), and behavior (66.7%) about vulva hygiene. Up to 70% of respondents did not experience pathological vaginal discharge. The bivariate analysis found a significant association between vulva hygiene knowledge, attitudes, and behavior with the incidence of pathological vaginal discharge (p-value < 0,05).